2008
DOI: 10.1007/s10311-008-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants in sludge-amended agricultural soils: a review

Abstract: Surfactants are included in different detergent formulations and are one of the most ubiquitous and important families of organic compounds. Although the generic term applies to a great number of products, 80% of their demand is covered by only ten types of compounds. The global surfactant market volume size is more than 18 million tons per year. Large quantities of surfactants are continuously released into the environment, where they can or cannot be degraded depending on their structure. The alkylbenzenesul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…This also demonstrates the need to investigate the composition and distribution of QACs in sludge, since they could re-enter the ambient environment through sludge land application and thus become potentially hazardous (Clarke and Smith, 2011;Fernández Cirelli et al, 2008).…”
Section: Qacs In Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…This also demonstrates the need to investigate the composition and distribution of QACs in sludge, since they could re-enter the ambient environment through sludge land application and thus become potentially hazardous (Clarke and Smith, 2011;Fernández Cirelli et al, 2008).…”
Section: Qacs In Sludgementioning
confidence: 99%
“…High concentrations of QACs would adversely impact the anaerobic digestion process by inhibiting methanogenesis, resulting in methane inhibition and volatile fatty acid (VFA) accumulation (Tezel et al, 2006(Tezel et al, , 2008, then affect the performance of activated sludge systems and in turn result in the decrease of the system efficiency. Moreover, risk from QACs-containing biosolids recycling on land cannot be ignored (Fernández Cirelli et al, 2008). Although risk assessment results indicated that this practice would not impact human health (Clarke and Smith, 2011), long-term research is needed to support its security and sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…In general, lower SRT decreased LAS elimination, while thermophilic conditions increased it. Literature results on the fate of LAS under anaerobic conditions are not clear either and some of the suggested factors affecting LAS removal are the formation of insoluble calcium and magnesium salts, aggregation with cationic surfactants, presence of other organic contaminants, and preexposure to aerobic conditions (Fernández-Cirelli et al 2008). …”
Section: Linear Alkylbenzene Sulfonatesmentioning
confidence: 99%
“…However, Scheunert and Korte (1985) found that a relatively low surfactant concentration (10 mg kg À1 in the uppermost 10 cm of soil) increased, rather than decreased, the mobilization of hydrophobic organic compounds, possibly by physically affecting near-surface soil sorption sites for water repellent compounds. By reducing surface tension and facilitating water entry into, and displacement of water-repellent substances from sidewalls of fine pores, surfactants at relatively low concentrations were thought to enhance movement of hydrophobic compounds (Fernández Cirelli et al, 2008;Laha et al, 2009). Doerr et al (2000) reported that prolonged hydration of a water repellent soil decreased water repellency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Haigh (1996) noted that electrolytes in solution increased the solubility and mobilization of hydrophobic compounds in soils treated with anionic and cationic surfactants. Electrolyte effects upon the efficacy of nonionic surfactants, in contrast, are thought to be minimal because charge interactions play no part in the formation of clusters of uncharged surfactants in solution (Haigh, 1996 To sustainably manage and protect soils in agricultural areas, more information is needed on the manner in which hydrophobic organic compounds (1) interact with all classes of surfactants (Fernández Cirelli et al, 2008), and (2) attach to and detach from particle surfaces (DeBano and Letey, 1969;Doerr et al, 2000). Unresolved questions still exist regarding movement of hydrophobic substances by water where electrolytes are present either in the soil or in irrigation water or rainfall.…”
Section: Introductionmentioning
confidence: 99%